Maternal Sensitivity, Mother-Child Attachment, and Cognitive Development of Preschool Children In Urban Poor Areas - Elien Surya Hadhyastuti; Neti - Hernawati (Department of Family and Consumer Sciences, Bogor Agricultural University, 2017)
This research aimed to analyze the influence of maternal sensitivity on mother-child attachment, and mother-child attachment on cognitive development. This research was conducted at Kelurahan Empang and Tegallega, Kota Bogor. The samples consist of 100 mothers and their child that were selected by proportional random sampling. The results showed that mother’s education length and maternal sensitivity has positive significant correlation with mother-child attachment. In addition, mother’s education length and income per capita has positive significant correlation with cognitive development. However, family size has negative significant correlation with mother-child attachment and also cognitive development. Child cognitive development was influenced by participation in early childhood education and mother’s education length. This research found that child cognitive development was not influenced by mother-child attachment.